Building the monocot tree of death: Progress and challenges emerging from the macrofossil‐rich Zingiberales. Issue 8 (2nd August 2018) - Smith, Selena Y.; Iles, William J. D.; Benedict, John C.; Specht, Chelsea D.
Abstract : Premise of the Study: Inclusion of fossils in phylogenetic analyses is necessary in order to construct a comprehensive "tree of death" and elucidate evolutionary history of taxa; however, such incorporation of fossils in phylogenetic reconstruction is dependent on the availability and interpretation of extensive morphological data. Here, the Zingiberales, whose familial relationships have been difficult to resolve with high support, are used as a case study to illustrate the importance of including fossil taxa in systematic studies. Methods: Eight fossil taxa and 43 extant Zingiberales were coded for 39 morphological seed characters, and these data were concatenated with previously published molecular sequence data for analysis in the program MrBayes. Key Results: Ensete oregonense is confirmed to be part of Musaceae, and the other seven fossils group with Zingiberaceae. There is strong support for Spirematospermum friedrichii, Spirematospermum sp. 'Goth', S. wetzleri, and Striatornata sanantoniensis in crown Zingiberaceae while " Musa " cardiosperma, Spirematospermum chandlerae, and Tricostatocarpon silvapinedae are best considered stem Zingiberaceae. Inclusion of fossils explains how different topologies from morphological and molecular data sets is due to shared plesiomorphic characters shared by Musaceae, Zingiberaceae, and Costaceae, and most of the fossils. Conclusions: Inclusion of eight fossil taxa expands the Zingiberales tree and helps explain the difficulty in resolving relationships. Inclusion of fossils was possible in part due to a large morphological data set built using nondestructive microcomputed tomography data. Collaboration between paleo‐ and neobotanists and technology such as microcomputed tomography will help to build the tree of death and ultimately improve our understanding of the evolutionary history of monocots.